Influence Digital Literacy towards Independence Study with Mediation Efficacy Self Student on Students of SMKN 31 Jakarta (International Journal of Education and Literature, 2025)
Education is the right of all people without exception. There are demands in the 21st century in the use of information and communication technology in everyday life, one of which is in education. Current education requires students to not only master basic knowledge, but also have the competence to learn independently, think critically, and be technologically literate. This study analyzes these three variables to determine the contribution of digital literacy to learning independence through self-efficacy. This study uses quantitative methods with primary data collected through questionnaires using Google Forms. This study involved 245 students as samples, selected using proportionate stratified random sampling technique. This study used SEM-PLS data analysis with SmartPLS software. The results of the research analysis show several significant findings. First, there is a positive and significant direct influence between digital literacy on learning independence. Second, there is a positive and significant direct influence between digital literacy and self-efficacy. Third, there is a positive and significant direct influence between self-efficacy on learning independence. Fourth, there is a positive and significant indirect effect between digital literacy on learning independence through self-efficacy.